COST AND LABOR PRODUCTIVITY OF BABY CHICKPEAS FARM - Eti Suminartika; Erna Rachmawati; Mohammad Arief Budiman; Yadi Nugraha Subandi (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
. The selling price of baby chickpeas is higher than non-baby chickpeas, the planting period of baby chickpeas is shorter than non-baby chickpeas because baby chickpeas are harvested at a young age, the relatively short harvest period of baby chickpeas requires more harvesting labour, while the availability of labour is relatively stable both from within the family and outside the family. The purpose of this study is to analyse the allocation, cost and labour productivity of baby chickpeas. The research uses a survey method, samples are taken randomly, the analysis used is mathematical analysis and descriptive analysis, the research was located in Lembang subdistrict in Bandung Barat Regency. The results of the study show that labour costs are the most of the total farming costs, which is 34 %, the majority of labour for harvesting activities is 64% of the total labour, the productivity of labour to output is 22 kg per man hour.